The Influence of Brand Trust on Purchase Decisions at Kopi Kenangan Batam - Aswar, Desi Natasya; Maldin, Siska Amelia (CV. Publikasi Indonesia, 2024)
This research aims to analyze the effect of Brand Trust on Purchasing Decisions at Kopi Kenangan Batam. The method used in this research is Simple Linear Regression. The sample to be studied was 100 respondents using the Slovin formula and purposive sampling technique. The characteristics of the sample studied were consumers located in Batam, had purchased Kopi Kenangan products 2 times and were at least 15 years old. The results of this study are expected to provide an overview of the Effect of Brand Trust on Purchasing Decisions at Kopi Kenangan Batam.